2017
DOI: 10.31357/vjm.v3i2.3636
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Migrations and Remittances: Evidence from Rural Sector of Sri Lanka

Abstract: Agriculture remains as one of the major sources of employment to the rural community in Sri Lanka. However, problems such as inadequate land and capital, low productivity and personal attitudes have pushed the rural agricultural worker to migrate out of the sector. As the decision to migrate is made at the household level, characteristics of the household shape up the decision to migrate and send remittances to the origin communities. Therefore, this study is an attempt to find the determinants of migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…But a study conducted by (Olatomide & Timothy, 2012) on the determinants ofremittancesfound that family size negatively and statistically significantly related. In the same way, study conduct by (Rathnayake & Dharmadasa, 2018) on the determinants of migration and remittance in Sri Lanka indicated that the family size of a migrant-sending household is negatively and statistically significantly related to remittance from migrants.…”
Section: Description Of Variables and Expected Signmentioning
confidence: 82%
See 2 more Smart Citations
“…But a study conducted by (Olatomide & Timothy, 2012) on the determinants ofremittancesfound that family size negatively and statistically significantly related. In the same way, study conduct by (Rathnayake & Dharmadasa, 2018) on the determinants of migration and remittance in Sri Lanka indicated that the family size of a migrant-sending household is negatively and statistically significantly related to remittance from migrants.…”
Section: Description Of Variables and Expected Signmentioning
confidence: 82%
“…This may be because households with large family sizes are more likely to engage in different livelihood sources and this may lead to lower incentives to rural-urban migrants to remit. Similarly, a study conduct by (Rathnayake & Dharmadasa, 2018) on the determinants of migration and remittance in Sri Lanka indicated that the family size of a migrant-sending household is negatively and statistically significantly related to remittance from migrants.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation